Power Flow Optimization of a Hybrid Energy System with Salp Swarm Algorithm - Darney, P. Ebby (Journal of Electronics and Informatics, 2023)
Electric energy has become more essential in the recent year for all human activities. Therefore the demand for electricity is increasing to an extreme. The non-conventional energy generation methods are attracting the energy suppliers as its design and implementation is comparatively simple than the conventional energy generation. However, the non-conventional energy sources are widely dependent to the nature. Hence the power supply regularity has become a questionable one for non-conventional energy systems. The design of hybrid power system allows addressing this issue by connecting more than one non-conventional energy system together for making a reliable power supply. To regulate the power supply generation on connecting more than system several optimization algorithms were implemented in the present hybrid energy systems. The proposed work aims to study the performances of the hybrid energy system connected with 3KW wind power generation with each 1KW power generation with solar system and battery backup of using salp swarm optimization algorithm. The experimental work is also extended to prove the efficiency of the proposed algorithm with the traditional particle swarm optimization and genetic algorithms.